Scabies Vaccine is Required, but Difficult to be Made - Simson Tarigan (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2007)
Sarcoptes scabiei, the mite causing scabies, infests human and at least 40 species of animals. The losses associated with the disease as a public health burden and economic losses are enormous because its prevalence is very high. The current available control by treating individuals diagnosed to have the disease is both ineffective and unpractical. Besides, dissatisfaction with the pharmacological control is escalating due to the development of resistance in the mites and rejection by consumers for animals products contaminated with drug residues. Vaccination is considered to be most the attractive alternative control although the availability of vaccine is still a long way off. Control of scabies by vaccination is considered to be feasible since animals recovered from the disease posses protective immunity against mite reinfestation. In addition, despite the fact that the mites reside not deeper than the unvascularised stratum corneum and they are not blood sucking parasites, they do ingest their host immunoglobulin.  Vaccine  for scabies,  as  for  other  ectoparasitic  diseases,  includes subunit vaccine  developed  from  mite protective antigen produced by recombinant technology. Identification of sarcoptic protective antigen which comprise the first step in the vaccine development impede by the lability and low abundance of the protective antigen, and the difficulty in obtaining sufficient amount of mites. Identification of sarcoptic protective antigen by conventional biochemical technique, although the technique has been successful for other parasites, has been unsatisfactory for S. scabiei. Identifying the protective antigen just among proteins having vital functions in the survival of mites and accessible by the effector arms of the host immune system seems to be a more feasible alternative. The allergens and membrane proteins lining the digestive tract of the mites seem to fulfil the criteria.   Key words: Sarcoptes scabiei, protective antigen, scabies vaccine